2018
DOI: 10.1007/s12155-018-9952-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Harvest Date and Cutting Length of Grass Ley and Whole-Crop Cereals on Methane Yield and Economic Viability as Feedstock for Biogas Vehicle Fuel Production

Abstract: Grass ley and whole-crop cereals used for biogas production are often finely chopped for subsequent ensiling and anaerobic digestion. Chopping can impact not only ensiling stability, digestibility and risk of process hick-ups in the digester but also harvesting capacity and fuel consumption. Based on field experiment data, the aim of this study was to investigate how three different nominal cutting lengths in the range of 3.5 mm to 12.5 mm impact methane yield and economic viability of grass ley and whole-crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
4
5
1
Order By: Relevance
“…The effect of the particle size on oDMMY shows that smaller particle size produces the optimum yield, and it is a crucial parameter during the optimisation of the biogas yields. This result is in line with what was earlier reported in related research works (Ajayi-Banji et al, 2020; Prade et al, 2019). The optimum FMMY was recorded at the bigger particle size; this result complement what was reported by Herrmann et al (2012) earlier.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The effect of the particle size on oDMMY shows that smaller particle size produces the optimum yield, and it is a crucial parameter during the optimisation of the biogas yields. This result is in line with what was earlier reported in related research works (Ajayi-Banji et al, 2020; Prade et al, 2019). The optimum FMMY was recorded at the bigger particle size; this result complement what was reported by Herrmann et al (2012) earlier.…”
Section: Resultssupporting
confidence: 94%
“…For oDMBY and oDMMY, their optimum yields were recorded at the same temperature and hydraulic retention time but with different particle sizes. Optimum oDMBY was recorded at a particle size of 4 mm, and this result agrees with what was recorded by earlier researchers when compared with 6 mm particle size (Ajayi-Banji et al, 2020; Kirby et al, 2020; Kulichkova et al, 2020; Prade et al, 2019). Compared with 2 mm particle size, it is contrary to what was earlier reported (Naegele et al, 2014; Nalinga and Legonda, 2016).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of storage time on methane yields has also been studied by [11,29,31,35]. All four studies reported that longer storage periods have a positive effect on methane yield.…”
Section: Ensiling For Anaerobic Digestionmentioning
confidence: 99%
“…Spence et al [7] examined substrates, including grass and triticale, at 38 • C for 20 days using a proprietary system with automated normalisation to STP (Anaero Technology, Cambridge, UK). Tests on the effect of harvest date and cutting length for grass and whole-crop rye and wheat were carried out by Prade et al [105] using the AMPTS II system, with values reported as dry gas at STP after 30 days of digestion. Allen et al [106] also employed AMPTS II for various substrates; the test duration is not explicitly stated but appears to have been 30 days.…”
Section: Methane Production Obtained From Short Retention Batch Testsmentioning
confidence: 99%